2017
DOI: 10.1590/abd1806-4841.20175076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surgical margins according to the histological type of basal cell carcinoma

Abstract: Basal cell carcinoma is the most common skin cancer in the world. The aim of this study was to evaluate the surgical margin of basal cell carcinoma and correlate this with its histologic subtype. A retrospective analysis of pathology laboratory records from 1990 to 2000 was performed and the following data was collected: age, sex, race, anatomical location, histological type, and state of the excision margins in 1,428 histopathological reports of basal cell carcinoma. Ages ranged from 6 to 99 years, with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…In our study, the most histologically famous subtype was, the nodular (60%), then superficial (17.5%), fibrosing (12.5%), and pigmented (10%). This matches with Godoy et al (10) who found that nodular type of BCC is the predominant one, it accounts for 60%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the most histologically famous subtype was, the nodular (60%), then superficial (17.5%), fibrosing (12.5%), and pigmented (10%). This matches with Godoy et al (10) who found that nodular type of BCC is the predominant one, it accounts for 60%.…”
Section: Discussionsupporting
confidence: 91%
“…The range of our patient's age was from 38-79 years, with a mean of 56.42±8.8 years, this matches with Godoy et al (10) , who suggested that the incidence of 55-75 years, is nearly 100 times higher in patients younger than 20 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 8 , 9 , 10 , 11 , 12 Head and neck tumors, especially in some topographic subregions and among less experienced professionals, appear to be associated more with compromised or inadequate margins compared to BCC in other sites. 11 , 12 , 13 , 14 Herein, our main objective was to evaluate the clinical and pathological factors associated with inadequate surgical margins in head and neck BCC through an institutional series in a tertiary oncological center.…”
Section: Introductionmentioning
confidence: 99%
“…The "gold standard" in BCC diagnostics is the pathomorphological study for determination of neoplasm type that is not only prognostic marker but also indicator of treatment method selection [12]. According to data of M. C. Cameron al.…”
Section: Discussionmentioning
confidence: 99%